Hubungan Onset Preeklamsia dengan Luaran Neonatus di RSUP Dr.Sardjito Yogyakarta - Harya Bayu Surawijaya; Eugenius Phyowai Ganap; Ahsanudin Attamimi (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2023)
Background: Preeclampsia is one of the leading causes of death for both mother and fetus. Preeclampsia is divided into two categories of onset, for preeclampsia that begins at gestational age below 34 weeks is called early onset preeclampsia and late onset preeclampsia begins after gestational age above 34 weeks. In early-onset preeclampsia, there is an imperfect remodeling of the maternal spiral arteries, resulting in abnormal uteroplacental perfusion, causing hypoxia and acidosis in neonates which can increase incidence of IUGR, incidence of neonatal sepsis, neonatal mortality, low APGAR scores and longer hospital length of stay.Objectives: To determine the relationship between maternal and neonatal outcomes with early-onset preeclampsia and late-onset preeclampsia.Methods: This study was a retrospective cohort design and the sampling method used consecutive sampling. The research subjects were divided into two groups, the early-onset preeclampsia group and the late-onset preeclampsia group who were treated and gave birth at the RSUP. Dr. Sardjito Yogyakarta in 2019-2020.Results and Discussion: This study had a total sample of 235 subjects consisting of 146 subjects in the EO-PE group and 89 subjects in the LO-PE group. The two groups had a significant difference in the incidence of neonatal death, the incidence of neonatal sepsis and length of stay (p<0.05), but there was no significant difference in the incidence of IUGR (p=0.527) and the incidence of low Apgar score (p=0.771).Conclusion: There was no difference in the incidence of IUGR and low Apgar score between mothers with EO-PE and mothers with LO-PE. The incidence of neonatal sepsis and the incidence of neonatal death in mothers with EO-PE is higher than in mothers with LO-PE which was influenced by gestational age and history of preeclampsia. The length of neonatal hospital stay in mothers with EO-PE is longer than that of mothers with LO-PE, it was influenced by the onset of preeclampsia and gestational age. Keywords: Early onset preeclampsia; late onset preeclampsia; neonatal outcome; neonatal sepsis; IUGR.